The role and place of automation and informatization systems in the development of the potential of the security and defense sector - Tkach, Mykola; Yasenko, Sergey; Boyko , Ruslan; Drynov, Dmytro (Social Development and Security, 2021)
The article is of interest to specialists in the field of military management, who study the development of automation systems of the armed forces and automated control systems. The aim of the article is to study the trends in the development of automation and informatization in the defense sector of the world and the existing market of information systems. In the process of achieving the goal of the study the following methods of scientific knowledge were used: analysis, synthesis, induction, deduction, comparison, system approach. The article shows the relevance of the development of automation and informatization systems in the defense sector. The experience of the Armed Forces of the Russian Federation in the implementation of these approaches is presented and the critical need for the introduction of information systems in the Armed Forces of Ukraine, which should deter armed aggression by the Russian Federation, is emphasized. Analysis of global market trends information systems that must meet the defense needs country of the world.. In connection with the development of technology, improvement of old and creation of new models of armaments and military equipment (unmanned systems, space technology, network-centric approach to building a command and control system, artificial intelligence, etc.), the use of which is not possible without modern information systems. the importance of their introduction in the Armed Forces of Ukraine in order to prevent backwardness from world trends in the competitive struggle of the world’s armies. These issues are especially important against the background of the war with Russia and Ukraine’s integration with NATO member countries, which are at the forefront of technological innovation in the world.